Genetic diversity and origin of Kazakh Tobet Dogs - Anastassiya Perfilyeva; Kira Bespalova; Yelena Kuzovleva; Rustam Mussabayev; Мamura Begmanova; Almira Amirgalyeva; Olga Vishnyakova; Inna Nazarenko; Assel Zhaxsylykova; Arailym Yerzhan; Yuliya Perfilyeva; Tatyana Dzhaembaeva; et al. (Scientific Reports, 2024)
Abstract The Kazakh Tobet is an indigenous Kazakh dog breed that has been used to guard livestock since ancient times. To understand the genetic structure and phylogenetic relationship of the Kazakh Tobet breed with other herding and livestock guarding dog breeds, we analysed short tandem repeat data of 107 Kazakh Tobet dogs from different regions of Kazakhstan and Mongolia, as well as whole genome sequencing data from two Kazakh Tobet dogs and 43 dogs from 24 working breeds. Our results indicate a high genetic diversity of the Kazakh Tobet, with the average number of alleles per locus ranging from 6.00 to 10.22 and observed heterozygosity ranging from 76 to 78%. The breed has a complex genetic structure characterised by seven different clusters. The neighbour-joining tree constructed based on 14,668,406 autosomal and the maximum likelihood tree based on mitochondrial D-loop sequences indicate a common genetic heritage between the Kazakh Tobet, the Central Asian Shepherd Dog and the Turkish Akbash. The presence of haplotype A18 in the Kazakh Tobets supports the hypothesis of the ancient origin of the breed, which was previously suggested by archaeological finds and written sources. These results provide an important genetic basis for the ongoing efforts to improve the Kazakh Tobet breed, to ensure its preservation as an independent genetic lineage and to recognise a breed on an international level.